Dakwah Kultural dalam Tradisi Maantar Jujuran Suku Banjar di Samuda Kotawaringin Timur (Cultural Dakwah in The Maantar Jujuran Tradition of The Banjar in Samuda Kotawaringin Timur) - Junita Junita; Mualimin Mualimin; Abubakar HM (Jurnal Dakwah Risalah, 2020)
This study aims to analyze cultural da’wah in the maantar jujuran tradition in the Banjar tribe in Samuda, Kotawaringin Timur Regency, Central Kalimantan Province. This study used a qualitative method with a phenomenological approach. The data were collected in three ways: observation, interviews, and documentary studies. This study found that the people of the Banjar tribe in Samuda understand that da'wah is not only limited to verbal delivery and the specificity of da'wah activities but also has an understanding that da'wah can be carried out indirectly with a cultural approach so that it is easily accepted by the community. The substance of the da'wah message in the maantar jujuran tradition represents the Banjar tribe in Samuda, who views the importance of a balance between fulfilling the needs of religious spirituality and spirituality with social human needs.